Investigation of the mineralogical petrographic, geochemical and physical properties of carbonate rocks from Ileia Prefecture and assesment for industrial applications - Tseni, X.; Koutsopoulou, E.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2012)
Research on carbonate rocks has been increasingly important during the last few decades, due to their numerous applications. In this paper, we examined the properties of Cretaceous carbonate rocks from the Olonos-Pindos Zone from Ileia Prefecture. The relationships between various physical properties and between petrographic features and physical properties were defined. This may lead to preliminary evaluation of carbonate rocks using microscopic investigation, which unlike the elaboration of a series of physical and mechanical properties, is a fast and inexpensive method. In addition, these properties, along with their geochemical characteristics, were used to assess the suitability of these carbonate rocks as fillers in various applications. Detailed petrographic study of the collected samples revealed the occurrence of biomicrite, intramicrite (mudstone και wackestone), biosparite (packstones and grainstones), intrasparite and rudstone. From the lower to the upper members, a decrease of the grain size of calcite is observed. X-ray diffraction study of the insoluble residue revealed the presence of quartz, chlorite, illite, smectite, and mixed layer illite-chlorite. The colour index of the investigated powdered samples is negatively influenced by the increase of organic and insoluble residue contents. The water absorption is inversely correlated with CaO content while moisture is positively correlated with insoluble residue. The grainstone and rudstone are characterized as ultra-high pure calcium limestones, except for Mg-rich crystalline dolomitic limestones. The packstones are calcium limestones of high to medium purity. Mudstones and wackestones are characterized as low calcium limestones. The results suggest that all the examined lithotypes can be used as soil conditioners and animal feed supplements; however only grainstones and rudstones are suitable for desulphurization of exhaust gasses and cement production.